Deteksi Molekuler Blastocystis sp. pada Babi Terinfeksi di Kabupaten Tabanan dan Badung, Provinsi Bali, Indonesia (MOLECULAR DETECTION OF BLASTOCYSTIS INFECTION IN PIGS AT TABANAN AND BADUNG DISTRICT, BALI PROVINCE, INDONESIA) - Mahendra, Doohan; Suwanti, Lucia Tri; Lastuti, Nunuk Dyah Retno; Mufasirin, Mufasirin; Suprihati, Endang; Yuniarti, Wiwik Misaco; Widisuputri, Ni Komang Aprilina (Jurnal Veteriner, 2020)
This study aims to identify morphology and molecular of Blastocystis infection in pigs in the Tabanan and Badung District, Bali Province, Indonesia. 100 samples of pig stool were taken, fifty samples from the Tabanan and fifty samples from Badung District. Blastocystis sp. isolated and identified microscopically and confirmed by polymerase chain reaction (PCR) as a molecular identification method. 63% (63/100) Blastocystis is found in pig feces from these two District by microscopic detection. Positive samples were found 27 samples from Badung and 36 samples from Tabanan. Five samples were taken from each District conducted a confirmation test using the PCR method and found 60% (6/10) positive samples, two samples from Badung and four samples from Tabanan. The results of this study indicate that in healthy pigs, they also contain parasites that have the potential to spread disease to humans. Therefore, the high incidence of Blastocystis in pigs can be an alarm or warning to prevent Blastocystis infection from livestock that can potentially to be a reservoir in the spread of disease.